STUDENTS’ PERCEPTION OF LEARNING ENGLISH THROUGH E-LEARNING MOODLE AT SMK KARYA BANGSA SINTANG - Juniar, Rima (Universitas PGRI Sumatera Barat, 2023)
The objective of this study is to discover students’ perceptions of using the Learning Management System (LMS) which is Moodle in learning English at SMK Karya Bangsa Sintang. This study uses quantitative research in the form of a survey study to carry out its goal. The original questionnaire used in this study is from Oktaria & Rahmayadevi (2021), modified by Khaerani (2022) which consists of 16 statements with a five-point Likert’s scale. The researcher collected the data by distributing the questionnaire using a google form to the students at SMK Karya Bangsa Sintang. This study will involve 100 students as the respondents from SMK Karya Bangsa Sintang, 51 students from grade XI, and 49 students from grade X. The findings of this study are expected to show a positive view from the students as they frequently use Moodle as their learning tool at school.